2020
DOI: 10.1080/22221751.2020.1844551
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of SARS-CoV-2 through faecal specimens

Abstract: Coronavirus disease 2019 (COVID-19) has become a pandemic with increasing numbers of cases worldwide. SARS-CoV-2, the causative virus of COVID-19, is mainly transmitted through respiratory droplets or through direct and indirect contact with an infected person. The possibility of potential faecal-oral transmission was investigated in this study. We collected 258 faecal specimens from nine provinces in China and detected the nucleic acid of SARS-CoV-2 using real-time RT–PCR. Vero cells were used to isolate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 23 publications
(27 reference statements)
0
55
0
2
Order By: Relevance
“…It is recommended to test anal swab, because in this study, except for nasopharyngeal swabs, SARS-CoV-2 was mostly detected in anal swabs. Moreover, several studies have characterized the presence of live virus in feces [17][18][19], indicating that SARS-CoV-2 may be transmitted by fecal route. Notably, Wang et al [19] failed to isolate virus in feces specimens collected at later time points of disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to test anal swab, because in this study, except for nasopharyngeal swabs, SARS-CoV-2 was mostly detected in anal swabs. Moreover, several studies have characterized the presence of live virus in feces [17][18][19], indicating that SARS-CoV-2 may be transmitted by fecal route. Notably, Wang et al [19] failed to isolate virus in feces specimens collected at later time points of disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they also work, which makes them equally exposed to infection as males. Moreover, it has been reported that the virus is excreted in the feces of infected human subjects 26 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the demonstrated challenges in capturing suspended live virus, respiratory transmission is now thought of as the primary mode of SARS‐CoV‐2 infection. By contrast, SARS‐CoV‐2 has been readily cultured from nasopharyngeal (NP) swabs, saliva, blood, stool, and semen 4,10‐12 . Mounting evidence indicates that COVID‐19 patients are most infectious within the first eight days following symptom onset, 4,12,13 with some outliers shedding live virus for up to 18 days 13,14 .…”
Section: Dear Editor Cowlingmentioning
confidence: 99%